Pengelolaan Pendidikan Karakter Siswa Berasrama di Sekolah Insan Cendekia Gorontalo - Robby Kharisma; Khairunnisa Khairunnisa (Jurnal Pendidikan Kewarganegaraan, 2018)
The basic thing of this research is finding the character values inculcated in the building of boarding students in MAN Insan Cendikia, the learning process of character building for boarding students in MAN Insan Cendikia Gorontalo, and monitoring and evaluation of the management of boarding students character building at MAN Insan Cendikia Gorontalo. The method used in this study is a qualitative method with a case study approach. Data sources from Principals, Dormitories coordinators, Academic Heads, Trustees of Class XII Science, Class X Students, English Language Teachers, Sports Section Coordinators, Science Section Coordinators, Head of Student Affairs and Quality Assurance Section Heads. Data is collected through observation, interviews, and document study.